Pedoman Kesehatan Dan Keselamatan Kerja Pada Industri Kerajinan Kerang Mutiara - Aminah Soleman; Farida D. Sitania (ARIKA, 2011)
Number of pearl shell craft industry in Ambon city until the year 2010 were 60 groups with a wide market share. But until now they do not have good references about the standardization of production processes and product standardization, one of which is occupational health and safety (OHS). The lack of standardization causes business owners paying less attention to environmental conditions and facility business. The problem that arises is that workers tend to work without sufficient knowledge, outside of the procedure and denied the use of personal protective equipment (PPE). These things cause the worker at risk of disruption, accidents and illnesses arising from working conditions. Socialization of the OHS and the use of PPE, the provision of PPE and occupational health facilities, and training on OHS and the use of PPE is the solution for problems occupational accidents in the creative industry of crafts pearl oysters in the city of Ambon